Acoustical characterization of the underground chapels of the new Holy Trinity church in the Fatima shrine, Portugal - António P. O. Carvalho (2011)
This paper presents the interior acoustic characterization of the Chapels of Reconciliation, underground chapels of the new Holy Trinity church in Fatima, Portugal. The results of in situ measurements are presented regarding Reverberation Time, RASTI (with and without the use of sound reinforcement system), sound levels and NC of the HVAC equipment and airborne sound insulation indexes between chapels. The results are compared with Portuguese Catholic churches of similar volume and the subjective opinion of users of these chapels is analyzed.